Genome Report: Genome sequence of 1S1, a transformable and highly regenerable diploid potato for use as a model for gene editing and genetic engineering - Thilani B Jayakody; John P Hamilton; Jacob Jensen; Samantha Sikora; Joshua C Wood; David S Douches; C Robin Buell (G3: Genes, Genomes, Genetics, 2023)
AbstractAvailability of readily transformable germplasm, as well as efficient pipelines for gene discovery are notable bottlenecks in the application of genome editing in potato. To study and introduce traits such as resistance against biotic and abiotic factors, tuber quality traits and self-fertility, model germplasm that is amenable to gene editing and regeneration is needed. Cultivated potato is a heterozygous autotetraploid and its genetic redundancy and complexity makes studying gene function challenging. Genome editing is simpler at the diploid level, with fewer allelic variants to consider. A readily transformable diploid potato would be further complemented by genomic resources that could aid in high throughput functional analysis. The heterozygous Solanum tuberosumAgrobacteriumAgrobacterium